2010
DOI: 10.1089/ten.tec.2009.0441
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Method for Evaluation of Geometric Fidelity for Anatomically Shaped Tissue-Engineered Constructs

Abstract: Quantification of shape fidelity of complex geometries for tissue-engineered constructs has not been thoroughly investigated. The objective of this study was to quantitatively describe geometric fidelities of various approaches to the fabrication of anatomically shaped meniscal constructs. Ovine menisci (n ¼ 4) were imaged using magnetic resonance imaging (MRI) and microcomputed tomography (mCT). Acrylonitrile butadiene styrene plastic molds were designed from each imaging modality and three-dimensional printe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Here we show that our previously documented approach to producing TE-TDR implants with circumferentially aligned collagen fibrils in the AF (15), combined with image-based design techniques to reproduce precise anatomy (22)(23)(24)(25)(26) yielded implants that integrated with the rat caudal spine, reproduced appropriate tissue structure, and generated a mechanically functional motion segment in the rat caudal spine.…”
mentioning
confidence: 91%
“…Here we show that our previously documented approach to producing TE-TDR implants with circumferentially aligned collagen fibrils in the AF (15), combined with image-based design techniques to reproduce precise anatomy (22)(23)(24)(25)(26) yielded implants that integrated with the rat caudal spine, reproduced appropriate tissue structure, and generated a mechanically functional motion segment in the rat caudal spine.…”
mentioning
confidence: 91%
“…39,81 Notably, multiple studies have demonstrated that optical scanning for validation can be incorporated in 3D bioprinters. 69,82 This offers the prospect of real-time assessment of print fidelity and immediate quality control/ quality analysis that may be useful for regulatory compliance. Ultimate clinical translation will also have to include strategies and regulations for cell sourcing, whether autologous or allogeneic, cell incorporation in the bio-ink or seeding on the printed construct, and implantation techniques to implant and fix the printed construct into the defect side.…”
Section: Current Challenges In Bringing 3d Bioprinting To Clinical Apmentioning
confidence: 99%
“…Briefly, those approaches include: decellularized matrix scaffold reseeded or not with cells [33][34][35][36][37][38][39], biodegradable synthetic polymers [40][41][42][43][44][45][46][47], biological protein based polymer [48][49][50][51], in vivo TEHV [52,53], hybrid TEHV manufacturing strategies (combining different approaches together) [53,54] and 3D printing of the valve [55][56][57][58]. A completely biological approach has also been recently developed by Cytograft™, allowing to produce a TEVH intended for transcatheter repair following an extended culture period in vitro [59].…”
Section: /26mentioning
confidence: 99%